CURRENT TRENDS IN FEEDING AND CARING FOR PREMATURE AND LOW BIRTH WEIGHT INFANTS - Laura Florescu; Oana Temneanu; Dana Mindru (Amaltea Medical Publishing House, 2014)
Low weight at birth is an important indicator of infant health due to the tight relationship between birth weight and infant mortality and morbidity. The diminishing of the mortality and morbidity rate requires information on the growth characteristics and caring requirements for this category of children. Regardless of the category they are in - prematures, Small for Gestational Age, delay in intrauterine growth - these children, due to their low weight at birth present a high risk to develop malnutrition, a reason why there should be known the energy requirements and the optimum nutrition principles, specifi c to them. Ensuring an early most favourable diet is the essential element in their care assistance.